Impact of deploying multiple point-of-care tests with a 'sample first' approach on a sexual health clinical care pathway. A service evaluation. (3rd February 2017) - Harding-Esch, Emma M; Nori, Achyuta V; Hegazi, Aseel; Pond, Marcus J; Okolo, Olanike; Nardone, Anthony; Lowndes, Catherine M; Hay, Phillip; Sadiq, S Tariq
Abstract : Objectives: To assess clinical service value of STI point-of-care test (POCT) use in a 'sample first' clinical pathway (patients providing samples on arrival at clinic, before clinician consultation). Specific outcomes were: patient acceptability; whether a rapid nucleic acid amplification test (NAAT) for Chlamydia trachomatis/Neisseria gonorrhoeae (CT/NG) could be used as a POCT in practice; feasibility of non-NAAT POCT implementation for Trichomonas vaginalis (TV) and bacterial vaginosis (BV); impact on patient diagnosis and treatment. Methods: Service evaluation in a south London sexual health clinic. Symptomatic female and male patients and sexual contacts of CT/NG-positive individuals provided samples for diagnostic testing on clinic arrival, prior to clinical consultation. Tests included routine culture and microscopy; CT/NG (GeneXpert) NAAT; non-NAAT POCTs for TV and BV. Results: All 70 (35 males, 35 females) patients approached participated. The 'sample first' pathway was acceptable, with >90% reporting they were happy to give samples on arrival and receive results in the same visit. Non-NAAT POCT results were available for all patients prior to leaving clinic; rapid CT/NG results were available for only 21.4% (15/70; 5 males, 10 females) of patients prior to leaving clinic. Known negative CT/NG results led to two females avoiding presumptive treatment, and one male receiving treatment directed at possible Mycoplasma genitalium infection causing non-gonococcal urethritis. Non-NAAT POCTs detected more positives than routine microscopy (TV 3 vs 2; BV 24 vs 7), resulting in more patients receiving treatment. Conclusions: A 'sample first' clinical pathway to enable multiple POCT use was acceptable to patients and feasible in a busy sexual health clinic, but rapid CT/NG processing time was too long to enable POCT use. There is need for further development to improve test processing times to enable POC use of rapid NAATs.